Clinical and Biomedical Spectroscopy and Imaging II 2011
DOI: 10.1364/ecbo.2011.80870n
|View full text |Cite
|
Sign up to set email alerts
|

Breast imaging using the Twente Photoacoustic Mammoscope (PAM): new clinical measurements

Abstract: Worldwide, yearly about 450,000 women die from the consequences of breast cancer. Current imaging modalities are not optimal in discriminating benign from malignant tissue. Visualizing the malignancy-associated increased hemoglobin concentration might significantly improve early diagnosis of breast cancer. Since photoacoustic imaging can visualize hemoglobin in tissue with optical contrast and ultrasound-like resolution, it is potentially an ideal method for early breast cancer imaging.The Twente Photoacoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Their results showed that they successfully detected malignancies in the two cases with IDC, while the PA images of the patient with cyst did not produce any significantly strong PA signals corresponding to the benign pathology. In vivo PA imaging was conducted by Heijblom et al [116] with Twente PAM for a patient with IDC where the malignant lesion was successfully located and visualized. In another in vivo study, performed by the same group [117] on ten patients with breast malignancy and two patients with a cyst, the results showed that the PA contrast generated by malignant pathology exceeded the corresponding X-ray contrast, whereas the two cases of cysts did not produce any significantly strong PA signals corresponding to benign pathology.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Their results showed that they successfully detected malignancies in the two cases with IDC, while the PA images of the patient with cyst did not produce any significantly strong PA signals corresponding to the benign pathology. In vivo PA imaging was conducted by Heijblom et al [116] with Twente PAM for a patient with IDC where the malignant lesion was successfully located and visualized. In another in vivo study, performed by the same group [117] on ten patients with breast malignancy and two patients with a cyst, the results showed that the PA contrast generated by malignant pathology exceeded the corresponding X-ray contrast, whereas the two cases of cysts did not produce any significantly strong PA signals corresponding to benign pathology.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…It images objects deep in tissue and provides resolution as in ultrasound imaging, and promises to be an alternative image modality for detecting angiogenic biomarkers of breast cancer [7][8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%